Pengaruh Bio-slurry Padat dan Pupuk Nitrogen terhadap Pertumbuhan dan Produksi Tanaman Kacang Hijau (Vigna radiataL.) - Leonardi. P Leonardi. P; Elza Zuhri; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to know the effect of the interaction of solid bio-slurry and nitrogen fertilizer, the influence of single factor of solid bio-slurry and nitrogen fertilizer and get better dosage of bio-slurry and nitrogen fertilizer to growth and production of green bean plants (Vigna radiata  L). This research has been conducted experimental farming Faculty of Agriculture University of Riau, Bina Widya road, Simpang Baru Village, District Tampan, Pekanbaru City. This research was conducted for 4 months from December 2016-March 2017. This research was conducted experimentally using Randomized Block Design (RBD) factorial composed of 2 factor. The first factor is the doses of bio-solid slurry consisting of 4 stages,that is B1: dose 2.5 ton.ha-1, B2: dose 5 ton.ha-1, B3: dose of 7.5 ton.ha-1and B4: dose of 10 ton.ha-1. The second treatment of nitrogen fertilizer (N) consists of 4 stages with the dose : N1: dose 25 kg.ha-1, N2: dose 50 kg.ha-1, N3: dose 75 kg.ha-1and N4: dose 100 kg.ha-1. Each was repeated 3 times so that there were 48 experimental units.Data obtained from the observations were statistically analyzed with the fingerprint and continued with the Duncan's multiple range test at 5%. Parameters observed were plant height, number of primary branch, age of flowering plant, harvest age, number of pods per plant, percentage of pods, production per m2 and weight of 100 seeds.The results showed that the administration of bio-solid slurry with nitrogen fertilizers to increase the growth of plant height, the number of pods per plant and yield per m2. The provision of bio-solid slurry at a dose of 7,5 ton.ha-1 may include flowering age, harvests and increased plant height, number of primary branches, number of pods per plant, pod percentage pithy, production per m2 and weight of 100 seeds. Applications of nitrogen fertilizer at a dose of 75 kg.ha-1 can accelerate flowering age, age and crop increased plant height, number of primary branches, number pods per plant, pods percentage pithy, production per m2 and a weight of 100 seeds. The provision of bio-slurry of solid dosage 7,5 ton.ha-1 and application of nitrogen fertilizer 75 kg.ha-1 provides the highest yield of the parameter plant height, number of primary branches, plant flower age, harvesting age, number of pods per plant, production per m2 and weight of 100 seeds.Keywords: green beans, organic manure, nitrogen fertilizer